SATIRIC PERFORMATIVITY OF STAND-UP COMEDY IN NIGERIA (2014)
Stand-up comedy, an oral dramatic performance commonly enacted by a solo-performer before a live audience, is today one of the most popular forms of performance in Nigeria. Studies of this performance genre have tended to examine its humorous and cultural dimensions to the neglect of its satiric import. This study, therefore, examined the satiric and performative devices deployed by selected stand-up comedians in Nigeria with a view to determining the role of stand-up comedy as a veritable source of socio-economic consciousness and a medium of social criticism. Schechner's performance theory and aspects of the Freudian and Jungian psychoanalytic theories were used to analyse the embodied behaviours of the performers and the rationale behind their phenomenal popularity with their audiences. Based on their profound employment of satiric and performative styles, four digital video discs containing 20 live recordings of performances were purposively selected for the study. These include Comedy Klinic Ward1 and Comedy Klinic Ward 2 by Godwin Komone?Gordons?14??, and A Nite of a Thousand Laughs Vol 15 and 16 jointly presented by Bright Okpocha (Basket Mouth ?2 ?), Francis Agoda (I Go Dye ?2 ?) and Godwin Komone?2?. These performances were subjected to performance and literary analyses. All the comedians orient to three types of satire, which are Juvenalian and Horatian in orientation, namely, political, social and religious. Basket Mouth evokes political satire, I Go Dye, social satire and Gordons, religious satire. While both Gordon and Basket Mouth utilise unshielded satiric (Horatian) humour, I Go Dye engages indirect satiric (Juvenalian) resources. In A Nite of a Thousand Laughs vol.15and16, Basket Mouth satirises Nigerian politicians, senior civil servants and other top government functionaries who are incompetent and who engage in bribery, corruption and political injustice through witticism, sarcasm, and paradoxical metaphors. Through burlesque, Gordons lampoons religious leaders, religious fanatics and the bourgeoisie in the society who use religion to perpetuate evil through violence and ethnic militia in the society. I Go Dye also criticises family conflicts which demonstrate the catastrophic effects of mindless pursuits of personal interests through farcical procedures. In all these performances, serious national issues are presented through the use of symbolism, caricature, subtle irony and humour. The performances are generally characterised by vocal dexterity, mimesis, blazer costume, zig-zagmovement, subject-constrained facial and bodily gestures, audience-dependent improvisation and interactivity. The stand-up comedies of Basket Mouth, I Go Dye and Gordons, which are a veritable mode of socio-political criticism in Nigeria, rely on nuanced deployment of both performative and linguistic devices which provoke laughter and aesthetic pleasure. Thus, these versions of comic performance function both as a cathartic device through which psychological and physical strains are eased out, and as a tool for critiquing social problems.